Longitudinal analysis of student learning motivation from past experiences to future career projections - Anggayana, I Wayan Agus (Priviet Social Sciences Journal, 2026)
This study investigates the motivational trajectory of Indonesian college students, examining the dynamic shifts that occur from their foundational past experiences to their articulation of future career ambitions. Employing an interpretive qualitative design rooted in narrative inquiry, this study analyzed rich, in-depth interview data from 13 participants (N=13), focusing on their lived motivational experiences across three distinct temporal phases: past, present, and future. Interpreted through the integrated frameworks of Self-Determination Theory (SDT) and the L2 Motivational Self System (L2MSS), the findings document a critical psychological evolution. Initial motivation (the ought-to self) was characterized as controlled and extrinsic, primarily stemming from filial obligation and the intense desire for external familial validation, such as "making parents proud.” The current academic phase marks a crucial shift toward identified regulation, characterized by a deliberate focus on self-discipline, procedural consistency and mastery of competencies. Looking forward, career projections reveal a transformation into the ideal self, transcending mere personal success to embrace the eudaimonic goals of social contribution and legacy creation, often channelled through entrepreneurship. This research highlights adversity as a powerful catalyst in this internalizing process, fostering increased autonomy and self-efficacy. It concludes that genuine, enduring motivation in this student population is inextricably linked to a long-term, integrated self-guide centered on meaningful community impact and relatedness, moving beyond purely material aspirations.